Nutritive Value, Digestibility, and Gas Production of Pennisetum purpureum Silage Supplemented with Saccharomyces cerevisiae and Lactobacillus plantarum - Riyanti, L.; Zahera, R.; Kisworo, A. N.; Wihansah, R. R. S.; Febriza, G. (Tropical Animal Science Journal, 2024)
The purpose of this study was to evaluate the use of Saccharomyces cerevisiae and Lactobacillus plantarum as silage additives and their combinations on the physico-chemical and microbiological quality of Pennisetum purpureum cv. Mott silage and assess fermentation characteristics, digestibility, and in vitro gas production. The experiment used a completely randomized design with 4 treatments and 5 replications. The treatments are: T0= dwarf elephant grass silage + 3% molasses, T1= T0 + S. cerevisiae, T2= T0 + L. plantarum, and T3= T0 + S. cerevisiae + L. plantarum. Variables measured were organoleptic, physical, microbial, nutrient composition, in vitro fermentation characteristics and nutrient digestibility, as well as total gas and methane productions. The result showed that all silages had good physical quality, low pH (